A very tangled web: public and private redux - Kennedy, Sheila Suess; Malatesta, Deanna (2010)
A recent Indiana Court of Appeals ruling raises significant concerns about the continuing erosion of the line between public and private, and the proliferation of the "unintended consequences" that flow from sectoral blurring. The authors use that case to introduce a broader discussion of the merits and drawbacks of public-private contracting, and the challenges in distinguishing among organisational types in an era that has seen considerable overlap in organizational characteristics. The authors survey the literature on these subjects and conclude with a discussion of the underappreciated financial, ethical, and constitutional implications of the erosion of clear sector distinctions. - Reproduced.
Keywords: Privatization